A new species of Minagenia Banks, 1934 (Hymenoptera, Pompilidae) from China, with the key to species - Ji, Xiao-Ling; Li, Chong-Yang; Ma, Li; Li, Qiang (Zootaxa, 2014)
Minagenia fulvifemoralis Ji et Ma, sp. nov. (Yunnan) is described and figured. Key to five species of the genus Minagenia Banks is given.